Impact of Christianization on the Process of Preaching the Gospel in Indonesia - Albert Leonarts Jantje Haans (INTERNATIONAL JOURNAL OF SOCIAL, POLICY AND LAW, 2021)
Churches and Christians can be affected by the impact of Christianization in preaching the gospel because the gospel is the joyful news of salvation in Jesus Christ. The statement of Christianization is one of the obstacles to accelerating the spread of the gospel. To conduct this research, the author uses qualitative research methods which is a library study. Data information is obtained from textbooks and literature as the main object. So, through this method, the writer describes, classifying, and compiling the relationship between humans and humans as well as The environment to get a complete and comprehensive understanding. Christianization is considered a way for Christians to influence, persuade and provoke the Islamic community according to the Christian lifestyle. Will this affect the evangelism process in Indonesia? Are Christians and churches affected by the impact of Christianization? Churches and Christians need to respond to this question because churches and Christians suspect that Christianization can